Self-reported Infection Status, Knowledge and Associated Factors of Monkeypox Among Men Who Have Sex with Men in Jiaxing, China - Yangyang Tian; Zhigang Hou; Guoying Zhu; Qianqian Zhang; Wutong Zhu; Hao Feng; Weizhe Pan; Qiang Li; Rui Ge; Zhongwen Chen (BMC, 2024)
Abstract Background As of September 2023, more than 1,000 cases of monkeypox (mpox) have been reported in China. Based on the available evidence, men who have sex with men (MSM) are at high risk for mpox infection. This study aimed to analyses the self-reported infection status, knowledge, attitude and influencing factors of monkeypox among MSM in Jiaxing City, China. Methods A web-based cross-sectional survey was conducted in September 2023 to gather data on participants' socio-demographic profiles, mpox-related knowledge, sexual behavior characteristics, and other potentially related information to mpox knowledge. Multivariate regression modeling was employed to analyze the factors influencing the level of mpox-related knowledge. Results A total of 562 MSM were recruited; 4.3% self-reported being HIV-positive, 83.3% of respondents had heard of mpox, and 2.3% of them reported having suspected symptoms. 89.7% of respondents were willing to be vaccinated against mpox, but only 24.8% had a high level of knowledge about mpox. The main factors influencing knowledge of mpox were education level, household registration, homosexual anal intercourse in the past 6 months, and taking the HIV pre-exposure prophylaxis (PrEP). Conclusions Knowledge of mpox among MSM living in the Jiaxing area needs to be enhanced, but willingness to get vaccinated is high. Educational level, household location, sexual behavior and PrEP use have important effects on knowledge of mpox. Individuals exhibiting symptoms indicative of suspected mpox had a diminutive consultation frequency, and it is imperative to augment screening efforts for mpox symptoms within specific demographic groups to prevent the underreporting of mpox cases.